Relevance Theory in Literature: Inferential Analysis of Audre Lorde’s Poem ‘From the House of Yemanjá’ - Ei Mon Kyaw (Educalitra: English Education, Linguistics, and Literature Journal, 2023)
In order to perform an inferential analysis using a relevance theory, this study pragmatically analyzes the poetry "From the House of Yemanjá" by Audre Lorde. Audre Lorde’s poetry entitled ‘From the House of Yemanjá’ is the subject of this study. An inferential analysis based on the relevance theory is employed in this study together with a qualitative methodology. The researcher served as the main analytical tool. The analysis's findings demonstrated how Audre Lorde's poetry From the House of Yemanjá used contextual inferences and poetic effects to highlight the physical settings, addressee, and characters. The researcher comes to the conclusion that Lorde created beautiful language by using contextual elements to symbolize the poetry.